2022
DOI: 10.3390/agriculture12070955
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SAR and Optical Image Fusion Methods in Oil Palm Crop Cover Classification Using the Random Forest Algorithm

Abstract: This paper presents an evaluation of land cover accuracy, particularly regarding oil palm crop cover, using optical/synthetic aperture radar (SAR) image fusion methods through the implementation of the random forest (RF) algorithm on cloud computing platforms using Sentinel-1 SAR and Sentinel-2 optical images. Among the fusion methods evaluated were Brovey (BR), high-frequency modulation (HFM), Gram–Schmidt (GS), and principal components (PC). This work was developed using a cloud computing environment employi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The topography of the area is heterogeneous, and some of the classes are located in the floodplain, which is typically undulating compared to developed and agricultural areas. Several studies have shown the importance of elevation data to increase the accuracy of the classified map [11,26,40,58]. In the same vein, radar backscatter was found to improve model performance because it can normalize or reduce the effects of the atmosphere, topography, instrument noise, etc., to provide consistent spatial and temporal comparisons [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topography of the area is heterogeneous, and some of the classes are located in the floodplain, which is typically undulating compared to developed and agricultural areas. Several studies have shown the importance of elevation data to increase the accuracy of the classified map [11,26,40,58]. In the same vein, radar backscatter was found to improve model performance because it can normalize or reduce the effects of the atmosphere, topography, instrument noise, etc., to provide consistent spatial and temporal comparisons [59].…”
Section: Discussionmentioning
confidence: 99%
“…Still, it has not been adequately evaluated by the remote sensing community as compared to more traditional pattern recognition algorithms. In addition, there have been observations about how the importance of variables varies depending on the data and ecosystem in question, necessitating further exploration [23,25,26]. To assist decision-makers in a variety of spatial planning applications (e.g., cropland management, irrigated agriculture intensification, flood vulnerability assessment, water management, or human settlement/resettlement planning in floodplains), the thematic LULC classes were created to represent the local characteristics of the semi-arid region, in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing is a science that investigates a variety of natural phenomena that occur on the surface of the Earth using sophisticated techniques to gather data from sensors mounted on various aerial platforms, from enormous satellites orbiting thousands of kilometers above the surface of the Earth to unmanned aerial vehicles (UAV) operating only a few meters above it. The electronic and technological advancements of both these platforms and their onboard sensors, as well as the numerous applications where remote sensing provides valuable information for decision-making, particularly in the determination of more precise land cover classifications, have seen significant advancements in recent years [24,25] Satellite images can now be obtained from a variety of platforms located across the globe [25]. The development of indicators to track and comprehend anthropogenic and natural processes necessitated using high-resolution and frequently updated land cover maps [26].…”
Section: Introductionmentioning
confidence: 99%
“…Electronic advancements in sensors and satellite platforms allow satellite spatial and temporal resolutions to continue to rise, reducing the time window for capturing information about a specific point on the Earth's surface and allowing for more continuous monitoring and analysis of the dynamics of various territories around the world. This temporal window is critical for agricultural area classification research, particularly for seasonal crops [25,27] Across the past 20 years, new opportunities for rapid mapping of land cover over vast areas have steadily emerged thanks to satellite photography with excellent spatial and temporal resolution [28]. The Copernicus Program, funded by the European Space Agency (ESA), now offers Sentinel, a global monitoring satellite platform that captures images of the entire Earth's surface every six days in various regions of the electromagnetic spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation